Implementasi Kurikulum Merdeka Dalam Membentuk Karakter Religius Peserta Didik Melalui Pembelajaran Fiqih - Anindya, Salsa; As Sajidah, Azka; Khadafiah, Harisa; Abdurrahmansyah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum in shaping students’ religious character through fiqh learning at MI Alamul Yaqin Palembang. The background of this research stems from the importance of instilling religious values from an early stage of education to provide students with a strong moral and ethical foundation. The Merdeka Curriculum is introduced as an educational policy that offers flexibility in the learning process, allowing lessons to be tailored to students’ needs, interests, and potential. This study employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The results show that the implementation of the Merdeka Curriculum in fiqh subjects is carried out through religious habituation activities such as collective prayer, congregational worship, Qur’an recitation, and direct practice of worship in daily life. Teachers play a crucial role as mentors, facilitators, and role models in shaping students’ religious character. Supporting factors include the availability of facilities and infrastructure, school religious programs, and parental involvement. Meanwhile, inhibiting factors involve limited instructional time, variations in students’ concentration levels, and teachers’ limited understanding of the new curriculum concept. This research is expected to serve as a reference for developing effective fiqh learning that focuses on the formation of students’ religious character.